Controls on boron isotope ratios in marine bivalve shells: Insights from a controlled experiment across pH and temperature gradients - Diana L. Thatcher; Joseph A. Stewart; Michèle LaVigne; Branwen Williams; Nina M. Whitney; Maya Giss; Teagan McMahon; Brittany Jellison; Katherine Guay; Heidi Franklin; Alan D. Wanamaker (Geochimica et Cosmochimica Acta, 2026)

Stress event alters skeletal structure but not geochemistry in a long-lived crustose coralline alga (Clathromorphum compactum) - Sophie M. Bernstein; Branwen Williams; Alan D. Wanamaker; Katherine Guay; Heidi Franklin; Michele LaVigne (Marine Biology, 2026)
Crustose coralline algae (CCA) are foundational species in shallow-water marine ecosystems, playing a critical role in their structural and ecological integrity. Additionally, their calcium carbonate skeletons serve as high-resolution paleoclimate archives, offering valuable insights into historical oceanic variability. Here, the effects of bleaching under controlled culture conditions on skeletal structure and geochemistry were investigated in the long-lived subarctic CCA Clathromorphum compactum . Cell wall thickness, interfilament crystal thickness, and skeletal Mg/Ca ratios derived from weight% were quantified in material formed before and after bleaching. Skeleton deposited following bleaching exhibited a distinct transition characterized by irregular cellular organization and was significantly thinner than pre-bleaching growth. Reductions in thickness occurred in individuals that later recovered as well as in those that died, indicating that calcification continued during physiological stress. In contrast, no significant difference in Mg/Ca ratio was detected between pre- and post-bleaching skeleton. These results suggest that C. compactum exerts some control over the geochemistry at its calcification site, maintaining stability despite environmental stressors that impact calcification. Thus, bleaching can leave pronounced structural irregularities in CCA skeletons, potentially affecting skeletal integrity, even when geochemical proxies remain unchanged.

Resistant calcification responses of Arctica islandica clams under ocean acidification conditions - Yi-Wei Liu; Alan D. Wanamaker Jr.; Sarah M. Aciego; Ian Searles; Thor Arne Hangstad; Melissa Chierici; Michael L. Carroll (Journal of Experimental Marine Biology and Ecology, 2023)

Eutrophication Drives Extreme Seasonal CO2 Flux in Lake Ecosystems - Ana M. Morales-Williams; Alan D. Wanamaker; Clayton J. Williams; John A. Downing (Ecosystems, 2021)

Trophic dynamics of a reservoir fishery following an introduction of a top predator: Insights from stable carbon and nitrogen isotopes - James J. Wamboldt; Alan D. Wanamaker; Hannah M. Carroll; Randall D. Schultz; Joseph E. Morris (Fisheries Management and Ecology, 2020)
Trophic dynamics and conceptual niche spaces of top piscivores were assessed using stable isotope analysis following the introduction of hybrid striped bass Morone saxatilis (Walbaum) × Morone chrysops (Rafinesque) into an established reservoir fishery devoid of gizzard shad, Dorosoma cepedianum (Lasueur). Hybrid striped bass were initially stocked into Three Mile Lake, Iowa as an attempt to biologically control pervasive yellow bass, Morone mississippiensis Jordan & Eigenmann, populations. From the analyses, it concluded that hybrid striped bass predominately targeted prey fish located in the littoral habitats of the reservoir and did not selectively consume yellow bass as intended. Bayesian isotope mixing models described the diets of hybrid striped bass to include a variety of prey fish, predominantly consisting of young bluegill Lepomis macrochirus and yellow bass. Food resource overlap among hybrid striped bass, largemouth bass, Micropterus salmoides Lacépède, and walleye, Sander vitreus (Mitchill), appeared substantial based on the isotopic niche overlap model. Results from this case study, in conjunction with the hindsight that yellow bass populations became prolific even with stockings of hybrid striped bass, suggest that their use to control yellow bass populations may not be a viable management strategy in southern Iowa.

Pacific climate influences on ocean conditions and extreme shell growth events in the Northwestern Atlantic (Gulf of Maine) - Alan D. Wanamaker; Shelly M. Griffin; Caroline C. Ummenhofer; Nina M. Whitney; Bryan Black; Rhys Parfitt; Erin E. Lower-Spies; Douglas Introne; Karl J. Kreutz (Climate Dynamics, 2019)

The value of crossdating to retain high‐frequency variability, climate signals, and extreme events in environmental proxies - Bryan A. Black; Daniel Griffin; Peter van der Sleen; Alan D. Wanamaker; James H. Speer; David C. Frank; David W. Stahle; Neil Pederson; Carolyn A. Copenheaver; Valerie Trouet; Shelly Griffin; Bronwyn M. Gillanders (Global Change Biology, 2016)
High‐resolution biogenic and geologic proxies in which one increment or layer is formed per year are crucial to describing natural ranges of environmental variability in Earth's physical and biological systems. However, dating controls are necessary to ensure temporal precision and accuracy; simple counts cannot ensure that all layers are placed correctly in time. Originally developed for tree‐ring data, crossdating is the only such procedure that ensures all increments have been assigned the correct calendar year of formation. Here, we use growth‐increment data from two tree species, two marine bivalve species, and a marine fish species to illustrate sensitivity of environmental signals to modest dating error rates. When falsely added or missed increments are induced at one and five percent rates, errors propagate back through time and eliminate high‐frequency variability, climate signals, and evidence of extreme events while incorrectly dating and distorting major disturbances or other low‐frequency processes. Our consecutive Monte Carlo experiments show that inaccuracies begin to accumulate in as little as two decades and can remove all but decadal‐scale processes after as little as two centuries. Real‐world scenarios may have even greater consequence in the absence of crossdating. Given this sensitivity to signal loss, the fundamental tenets of crossdating must be applied to fully resolve environmental signals, a point we underscore as the frontiers of growth‐increment analysis continue to expand into tropical, freshwater, and marine environments.

A late Holocene paleo-productivity record in the western Gulf of Maine, USA, inferred from growth histories of the long-lived ocean quahog (Arctica islandica) - Alan D. Wanamaker; Karl J. Kreutz; Bernd R. Schöne; Kirk A. Maasch; Andrew J. Pershing; Harold W. Borns; Douglas S. Introne; Scott Feindel (International Journal of Earth Sciences, 2009)

Experimentally determined Mg/Ca and Sr/Ca ratios in juvenile bivalve calcite for Mytilus edulis: implications for paleotemperature reconstructions - Alan D. Wanamaker Jr; Karl J. Kreutz; Tiffany Wilson; Harold W. Borns Jr; Douglas S. Introne; Scott Feindel (Geo-Marine Letters, 2008)

Coupled North Atlantic slope water forcing on Gulf of Maine temperatures over the past millennium - Alan D. Wanamaker; Karl J. Kreutz; Bernd R. Schöne; Neal Pettigrew; Harold W. Borns; Douglas S. Introne; Daniel Belknap; Kirk A. Maasch; Scott Feindel (Climate Dynamics, 2008)